Measurements of Ice Shelf Water beneath the front of the Ross Ice Shelf using gliders. Issue 74 (1st December 2017) - Nelson, Monica J.S.; Queste, Bastien Y.; Smith, Inga J.; Leonard, Gregory H.; Webber, Benjamin G.M.; Hughes, Kenneth G.
ABSTRACT: Measurements made by an underwater glider deployed near the Ross Ice Shelf were used to identify the presence of Ice Shelf Water (ISW), which is defined as seawater with its potential temperature lower than its surface freezing point temperature. Properties logged by the glider included in situ temperature, electrical conductivity, pressure, GPS location at surfacings and time. For most of the first 30 recorded dives of its deployment, evidence suggests the glider was prevented from surfacing due to being under the ice shelf. For dives under the ice shelf, farthest from the ice shelf front, ISW layers of varying thicknesses and depth locations were observed; between 2 m thick (centred at 231 m depth) to >93 m thick (centred at >360 m). For dives under the ice shelf, close to the ice shelf front, either no ISW was observed or ISW layers were centred at shallower depths (116–127 m). Thicker ISW layers (e.g. up to 250 m thickness centred at 421 m) were observed for some glider dives in open water in front of the Ross Ice Shelf. No in situ supercooling (water colder than the pressure-dependent freezing point temperature) was observed.